2019
DOI: 10.12659/msm.917115
|View full text |Cite
|
Sign up to set email alerts
|

Xiaoai Jiedu Recipe Inhibits Proliferation and Metastasis of Non-Small Cell Lung Cancer Cells by Blocking the P38 Mitogen-Activated Protein Kinase (MAPK) Pathway

Abstract: This work was supported by the Nanjing Medical Science and Technology Development Foundation Background: Lung cancer is the leading cause of cancer deaths in the world. Its major histopathological subtype is non-small cell lung cancer (NSCLC). Xiaoai Jiedu recipe (XJR) is a traditional Chinese medicine formula that can suppress growth and invasion of tumor cells. Here, we assessed the antitumor effect of XJR on NSCLC explored the underlying mechanisms. Material/Methods: Three concentrations of XJR (low, middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…XJR is composed of 7 different herbal ingredients: Hedyotis diffusa (20 g), Radix pseudostellariae (15 g), Bombyx batryticatus (10 g), Cremastra appendiculata (10 g), Centipede (3 g), Radix ophiopogonis (12 g), and Akebia trifoliata Koidz (12 g). Decoction of XJR (2 g/ mL) was prepared according to the standard method, 8 diluted with saline (v/v, 1:1), and stored at 4°C for later use. Cisplatin was purchased from the Shanghai Yuanye Biotechnology Co., Ltd (Shanghai, China).…”
Section: Drugs and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…XJR is composed of 7 different herbal ingredients: Hedyotis diffusa (20 g), Radix pseudostellariae (15 g), Bombyx batryticatus (10 g), Cremastra appendiculata (10 g), Centipede (3 g), Radix ophiopogonis (12 g), and Akebia trifoliata Koidz (12 g). Decoction of XJR (2 g/ mL) was prepared according to the standard method, 8 diluted with saline (v/v, 1:1), and stored at 4°C for later use. Cisplatin was purchased from the Shanghai Yuanye Biotechnology Co., Ltd (Shanghai, China).…”
Section: Drugs and Reagentsmentioning
confidence: 99%
“…The medicated serum was prepared according to the protocol. 8 Briefly, 24 adult Sprague-Dawley rats (6~8 weeks; 220~250g) were divided into XJR (N = 12) and control (N= 12) groups. The rats were fasted for 12 hours.…”
Section: Preparation Of Medicated Serummentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, XJR affected the expression of apoptosis-related proteins and decreased the expression of p-p38, p-ERK, and p-JNK. In other words, XJR promoted apoptosis and suppressed proliferation of A549 cells by blocking p38/MAPK pathway [ 60 ]. Zhao et al showed that Xiaoji decoction (XJD) inhibited growth of lung cancer cells by increasing phosphorylation of AMP-activated protein kinase alpha (AMPKα).…”
Section: Resultsmentioning
confidence: 99%
“…Chinese herbal medicine Wenxia Changfu formula reverses cell adhesion-mediated drug resistance in lung cancer. Xiaoai Jiedu recipe can inactivate p38 MAPK signaling pathway in NSCLC cells to inhibit its proliferation and metastasis ( 174 ). Recent studies have found that CERS6 has important roles in lung cancer migration and metastasis, which proves that the miR-101-CERS6 pathway can be targeted, with potential benefits provided for affected patients ( 175 ).…”
Section: Resultsmentioning
confidence: 99%